Analysis of community communication, processes and psychological elements: Las Piñas citadel case of the Milagro City – Ecuador - Viejó Mora, Israel (2022)
The research aims to analyze the processes and psychological elements of communication that are generated in the citadel Las Piñas of the city of Milagro, for which a descriptive design has been applied with a quali-quantitative approach through in-depth interview and surveys, for which a sample of 6 community leaders and 323 residents was selected. The results showed a lack of knowledge about community participation by the leaders as well as the residents, evidenced rather coordinated cooperation activities such as meetings, mingas and brigades to manage specific needs of the community. Regarding the communication processes, these are limited to the municipal authorities and internally in the community the actions are personal or through WhatsApp. In addition, with respect to the psychological elements, there is a total ignorance of the legal regulations on the part of the community product of the unfavorable perception which declines the attitudes and values of the citizenship in the face of these phenomena. All this hinders an adequate participatory movement.